A Privacy-Preserving Reputation Evaluation System with Compressed Revocable One-Time Ring Signature (CRORS) - Xu Han; Dawei Zhang (Mathematics)
Reputation evaluation systems are vital for online platforms, helping users make informed choices based on the trustworthiness of products, services, or individuals. Ensuring privacy and trust in these systems is critical to allow users to provide feedback without fear of retribution or identity exposure. The ring signature (RS), enabling anonymous group-based signing, has garnered attention for building secure and private reputation systems. However, RS-based systems face significant challenges, including the inability to identify malicious users who repeatedly sign the same message, the lack of mechanisms to reveal identities involved in unlawful activities, and a linear growth in signature size with the number of ring members, which poses storage challenges for certain applications. Addressing these limitations, we propose a compressed revocable one-time ring signature (CRORS) scheme leveraging compressible proofs under the Diffie–Hellman Decision and Discrete Logarithm assumptions in the random oracle model. CRORS ensures anonymity, unforgeability, one-time linkability, non-slanderability, and revocability. The one-time linkability feature prevents double-signing, while revocability enables identity disclosure for regulatory enforcement. Additionally, the signature size is reduced to <semantics>O(logn)</semantics>, significantly enhancing storage efficiency. These improvements make CRORS particularly suitable for blockchain-based reputation systems with ever-growing storage demands. Theoretical analysis validates its effectiveness and practicality.